AjTGFβ alleviates V. splendidus-induced inflammation through SMADs pathway in Apostichopus japonicus. Issue 134 (March 2023) - zhen, Zhang; wenwen, Ye; guanghui, Han; chenghua, Li; zhimeng, Lv
Abstract: The inhibition of inflammatory response is an essential process to control the development of inflammation and is an important step to protect the organism from excessive inflammatory damage. As a pleiotropic cytokine, transforming growth factor beta (TGF-β) plays a regulatory role in inhibiting inflammation in vertebrates. To investigate the role of TGF-β in the regulation of inflammation in invertebrates, we cloned and characterized the TGF-β gene from Apostichopus japonicus via rapid amplification of cDNA ends, and the sample was designated as AjTGF-β. For Vibrio splendidus -challenged sea cucumbers, the expression of AjTGF-β mRNAs in coelomocytes decreased at 96 h (0.27-fold), which was contrary to the trend of inflammation. AjTGF-β was expressed in all tissues with the highest expression in the body wall. When AjTGF-β was knocked down by using small interfering RNA (siRNA-KD) to 0.45-fold, AjSMAD 2/3 and AjSMAD6 were downregulated to 0.32- and 0.05-fold compared with the control group, respectively. Furthermore, when the damaged sea cucumber was challenged by V. splendidus co-incubated with rAjTGF-β, the damage area had no extensive inflammation, and damaged repair appeared at 72 h compared with the Vs + BSA group, in which the expression of AjSMAD 2/3 was upregulated by 1.35-fold. Under this condition, AjSMAD 2/3 silencing alleviated rAjTGF-β-induced damage recovery. Moreover, rAjTGF-β slightly induced the collagen I expression from 6.13 ng/mL to 7.84 ng/mL, and collagen III was upregulated from 6.23 ng/mL to 6.89 ng/mL compared with the Vs + BSA group. This finding indicates that AjTGF-β negatively regulated the inflammatory progress and accelerated the repair of damage by AjSMADs to regulate the collagens expression. Highlights: The first TGF-β was identified from Apostichopus japonicus. AjTGF-β mRNA levels displayed higher abundance in body wall. rAjTGF-β accelerate the sea cucumber inflammation damaged repair. AjSMAD 2/3 silencing alleviated rAjTGF-β-induced damage recovery. rAjTGF-β was slightly induced the collagen I/III expression.